Kant and the Creation of Freedom: A Theological Problem. By Christopher J. Insole - Lee, Hoon J. (The journal of theological studies, 2014)
Christopher J. Insole argues that the question ‘how can it be said that human beings are free, given that they are created by God?’ was not only formative for Kant's pre-critical development but also a major factor in his mature thought (p. 1). In posing the question, Insole looks to highlight two elements. First, there is significant continuity and a natural progression from Kant's pre-critical to his critical philosophy. Second, religion and theology play an integral role in Kant's critical philosophy., The first three chapters address Insole's first objective: recounting the theological dilemma of God's freedom, which does not require the possibility to do otherwise, and human freedom, which necessitates the ability to do otherwise.